Income‐Level and Immigrant Status Are Associated With Discontinuation of Evidence‐Based Secondary Prevention Therapies After Myocardial Infarction - Joel Ohm; Kevin Ma; Sara Freyland; Ali Yari; Tomas Jernberg; Per Svensson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Mechanisms for worse prognosis after myocardial infarction in low socioeconomic status are unclear. We therefore investigated the association between socioeconomic status and discontinuation of evidence‐based secondary prevention drug therapies. Methods All patients with a first‐ever myocardial infarction, on treatment with a statin (n=60 717), antithrombotic therapy (n=65 862), or a renin‐angiotensin‐aldosterone‐system inhibitor (n=51 486) at the routine 1‐year visit in SWEDEHEART (Swedish Web‐System for Enhancement and Development of Evidence‐Based Care in Heart Disease Evaluated According to Recommended Therapies) between January 2006 and mid‐2020 were included in this population‐based nationwide cohort study. Individual‐level socioeconomic status was measured by disposable income quintile, region of birth, and educational level. Outcomes were discontinuation (>180 days without a new prescription claim) of statins, antithrombotic therapies, and renin‐angiotensin‐aldosterone‐system‐inhibitors. Bias‐minimized multivariable adjusted hazard ratios (aHRs) were estimated during follow‐up until December 2020. Results Discontinuation occurred more often in the lowest versus highest income quintile for statins (aHR, 1.25 [95% CI, 1.20–1.31]), antithrombotic therapy (aHR, 1.26 [95% CI, 1.20–1.32]), and renin‐angiotensin‐aldosterone‐system inhibitors (aHR, 1.32 [95% CI, 1.26–1.39]). Discontinuation of statins was more frequent among immigrants (versus nonimmigrants) born in other Nordic (aHR, 1.24 [95% CI, 1.17–1.32]), other European (aHR, 1.40 [95% CI, 1.33–1.47]), Asian (aHR, 1.45 [95% CI, 1.36–1.56]), and other world regions (aHR, 1.63 [95% CI, 1.45–1.84]). Associations between immigrant background and discontinuation of antithrombotic therapies and renin‐angiotensin‐aldosterone‐system inhibitors were even stronger. Lower (versus tertiary) educational level was inversely associated with discontinuation of secondary prevention drug classes. Conclusions Despite Swedish universal health care, discontinuation of evidence‐based drugs post myocardial infarction is strongly associated with disposable income and immigrant background. Further study on strategies to improve adherence in low socioeconomic status post myocardial infarction is warranted.